The effect of additional sucrose on the value of tensile strength and elongation of chicken legs gelatin film - Begum Fauziyah; Dyah Fatimatussholichah; Aldila Raudatus Syarifah; Burhan Ma'arif (Wolters Kluwer Medknow Publications, 2023)
Gelatin is a clear, flavorless, and colorless biopolymer formed by the denaturation of collagen protein in animal tissues. Gelatin is an important ingredient in the manufacture of capsule shell films. The tensile strength and elongation values of gelatin film indicate its quality. Sucrose is one of the ingredients that can affect the tensile strength and elongation of the gelatin film. To determine the effect of adding sucrose on the tensile strength and elongation of the chicken leg skin gelatin film. To extract the gelatin, clean, sliced chicken leg skin was freeze-dried, ground into powder, and extracted. The characteristics of chicken skin gelatin were measured using Fourier-transform infrared, and the data were read in the 4000-400 cm − 1 range for 32 scans. Pouring the solution into a mold, flattening it, and drying it at 40°C results in a film that has been tested for tensile strength and elongation. Gelatin films with a 30% sucrose addition had the best tensile strength and elongation values, with a tensile strength of 3.03 MPa and an elongation of 152.02%. Sucrose alters the tensile strength and elongation of chicken leg gelatin film. 30% sucrose provides better tensile and elongation strength.